Modified acupuncture therapy, long-term acupoint stimulation versus sham control for weight control: a multicenter, randomized controlled trial - Dai, Liang; Wang, Miao; Zhang, Ke-Pei; Wang, Lin; Zheng, Hui-Min; Li, Chun-Bo; Zhou, Wen-Jun; Zhou, Shi-Gao; Ji, Guang (Frontiers in Endocrinology, 2022)
Objective: Long-term acupoint stimulation, also called embedding acupuncture, is a modified acupuncture technique. The preliminary results have demonstrated its efficacy in body weight control. However, the low quality of available trials limited its application. This study aimed to evaluate the efficacy and safety of long-term acupoint stimulation in body weight control by using a randomized, parallel, sham control clinical trial design. Methods: This was a randomized, single-blinded, sham-controlled clinical trial including 84 adult participants (18-60 years) with body mass index ≥ 24 kg/m2 conducted in three general hospitals in Shanghai, China. Participants were equally assigned to receive long-term acupoint stimulation or sham long-term acupoint stimulation once per ten days, eight times in total. After completion, an additional intervention with a three-month follow-up period was set to examine the continued effect. The primary outcome was the change of body weight from baseline to treatment endpoint within the intention-to-treat analysis. Secondary outcomes contained changes in waist-to-hip ratio, lipid metabolism, and contents of visceral and subcutaneous adipose tissues. Results: From May 14th, 2018 to November 3rd, 2019, 84 participants of 201 screened individuals met the eligibility, randomized, and analyzed (42 participants in each group). From baseline to treatment endpoint, the body weight reduction in the long-term acupoint stimulation group was significantly larger than in sham control (net difference: 1.57kg, 95% CI: 0.29-2.86, p = 0.012). The superior weight reduction effect persisted in the follow-up period (net difference: 3.20 kg, 95% CI: 1.17-5.21, p = 0.001). Long-term acupoint stimulation therapy also showed improvement in triglyceride and subcutaneous adipose tissue compared with sham control. One participant in the long-term acupoint stimulation group reported a slightly uncomfortable and tingling sensation after the ninth treatment. No other adverse event was documented. Conclusion: Long-term acupoint stimulation, the modified acupuncture technique, was safe and effective in body weight control. It could be served as the alternative choice of classical acupuncture for obesity management. Clinical Trial Registration: www.chictr.org.cn, identifier ChiCTR1800015498